(3SHd GdgOi hGdQTGO aj SjQI NjQ GdYHGO hPcQ aVGFdg hCYdGe fHhJg hCaYGdg hCMhGdg aj GdeHOC hGdeYGOs - (3GdTeS GdTGej , eMeO Hf jhSa Hf Ydj Hf jhSa, TeS GdOjf,J (B942 (3g` s
(3ChdgG (B:s
(3jHJOF HGdHG GdChd ai fHY GdeGA GdWghQ ef Hjf CUGHYg Udi Gddg Ydjg hSde ef HGH LeGY eYLRGJg s
(3BNQgG (B:s
(3hjfJgi gPG GdLRA HBNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B131s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B81 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs